2015
DOI: 10.1021/jacs.5b09966
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Catalysis Achieved through in Situ Desymmetrization of an Achiral Iron Catalyst Precursor

Abstract: Stereoselective catalysis is described that proceeds with catalyst control but without the need to synthesize preformed chiral catalysts or ligands. Iron-based catalysts were discovered to effect the stereoselective polymerization of lactides starting from a single achiral precursor and the proper choice of an achiral silanol additive. Spectroscopic analysis of the polymer revealed that the stereoselectivity originates from an enantiomorphic site rather than a chain end stereocontrol mechanism. Iron intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Nature often couples proton responsivity and redox-activity, preferring the more efficient proton coupled electron transfer (PCET) 5,6 to transferring each moiety separately. The function of hemilability in both biological and synthetic systems [9][10][11][12][13][14][15] is primarily to stabilize otherwise unfavorable intermediates by filling a vacant coordination site. This variable binding motif can be found stabilizing resting states, 16 actively participating in catalytic cycles, 4,17 or stabilizing high energy intermediates in enzymes and catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nature often couples proton responsivity and redox-activity, preferring the more efficient proton coupled electron transfer (PCET) 5,6 to transferring each moiety separately. The function of hemilability in both biological and synthetic systems [9][10][11][12][13][14][15] is primarily to stabilize otherwise unfavorable intermediates by filling a vacant coordination site. This variable binding motif can be found stabilizing resting states, 16 actively participating in catalytic cycles, 4,17 or stabilizing high energy intermediates in enzymes and catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…2) 19 and the polymerization of lactides facilitated by hemilabiity in the pyridinediinmine (PDI) ligand. 14 Lastly, the resurgence in metallocrown ethers as switchable catalysts has recently been reviewed. 15…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, silyl‐functionalised Fe II β‐diketiminates and anionic Fe II alkoxides were tested successfully as catalysts in solution or as bulk catalysts . In recent years, Byers et al developed redox‐controlled bis(imino)pyridine iron bis(alkoxide) complexes as polymerisation catalysts, which allowed the reaction to be stopped by oxidation and restarted by subsequent reduction . In addition to iron‐centred ROP catalysis, Atkinson et al developed 1,1′‐ferrocenediyl salicylaldimine ligands for titanium‐based complexes, and Fraser et al established polylactide‐supported tris(dibenzoylmethane)‐centred iron complexes, in which the iron atom functions as a protecting group for the β‐diketones …”
Section: Introductionmentioning
confidence: 99%
“…Long et al demonstrated that the reduction of an α‐diimine Ni II complex could modulate the branching density of the resulting polyethylene by up to 30 % (Scheme , III ) . It should be noted that this redox‐control strategy has been extensively studied in ring‐opening polymerization of cyclic esters, but has only been recently extended to other types of polymerization reactions …”
Section: Introductionmentioning
confidence: 99%
“…[18] It should be noted that this redoxcontrol strategy has been extensively studied in ring-opening polymerization of cyclic esters, but has only been recently extended to other types of polymerization reactions. [19][20][21][22][23][24][25][26][27] Two strategies are employed to achieve in situ redox control: (1) the oxidation or reduction of a preinstalled ferrocene unit; and (2) the oxidation or reduction of the redox-active metal center.…”
Section: Introductionmentioning
confidence: 99%